Applications of the Speed–Accuracy Trade-off and Impulse-Variability Theory for Teaching Ballistic Motor Skills. Issue 6 (2nd November 2019) - Molina, Sergio L.; Bott, Tim S.; Stodden, David F.
ABSTRACT: Bridging the gap between innovative research and teaching is a fundamental necessity for physical education practitioners to promote motor skill development and competency. This requires practitioners to understand, synthesize, and appropriately apply relevant research from different academic domains in their instructional environments. Ballistic motor skills such as kicking, throwing, and striking are fundamentally integrated into many games and sports and provide a foundation for physical activity and fitness for children and adults. Unfortunately, many individuals do not attain a high level of competence in these types of skills by adolescence. The purpose of this review is to integrate theory, pedagogical best practices, and current evidence on studies relating to Fitts' Law's application of the speed–accuracy trade-off and impulse-variability theory to provide an evidence-based framework for promoting effective instructional environments for learning ballistic motor skills.